2013
DOI: 10.1021/bm4002409
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylated Micelles for a Ribavirin Prodrug Targeting to Hepatocytes

Abstract: Polymeric micelles potentially able to carry to hepatocytes a ribavirin (RBV) prodrug, exploiting the presence of carbohydrate receptors, that is, ASGPR, were prepared starting from a galactosylated polylactide-polyaminoacid conjugate. This latter was obtained by chemical reaction of α,β-poly(N-2-hydroxyethyl) (2-aminoethylcarbamate)-dl-aspartamide (PHEA-EDA) with polylactic acid (PLA), and subsequent reaction with lactose, obtaining PHEA-EDA-PLA-GAL copolymer. To enhance the entrapment into obtained nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…a,b-poly(N-2-hydroxyethyl)(2-aminoethylcarbamate)-D,Laspartamide (PHEA-EDA) copolymer is an appropriate starting macromolecule to design novel amphiphilic copolymers for biomedical application (Craparo et al, 2008;Craparo et al, 2013a;Licciardi et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…a,b-poly(N-2-hydroxyethyl)(2-aminoethylcarbamate)-D,Laspartamide (PHEA-EDA) copolymer is an appropriate starting macromolecule to design novel amphiphilic copolymers for biomedical application (Craparo et al, 2008;Craparo et al, 2013a;Licciardi et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Galactosylated PHEA-EDA-PLA copolymer (PHEA-EDA-PLA-GAL) was synthesized by a reductive amination of lactose with primary amine functions of PHEA-EDA-PLA in the presence of sodium cyanoborohydride, according to the procedure previously published and spectroscopic data were in agreement with the attributed structure (Craparo et al, 2013a The M w was found to be 24.3 kDa M w =M n ¼ 1:66 À Á . The amount of GAL grafted onto PHEA-EDA-PLA-GAL copolymer measured by using anthrone-sulphuric acid colorimetric method was 0.86 wt% (corresponding to 1.22 mol%) (Craparo et al, 2013a;Song et al, 2009).…”
Section: Phea-eda-pla-gal Synthesismentioning
confidence: 96%
See 3 more Smart Citations